2014
DOI: 10.1093/heapol/czu103
|View full text |Cite
|
Sign up to set email alerts
|

‘Excuse me, sir. Please don’t smoke here’. A qualitative study of social enforcement of smoke-free policies in Indonesia

Abstract: Objective District policies were recently put into place in Indonesia prohibiting smoking in public spaces. This study sought to (1) assess participants’ general knowledge of secondhand smoke (SHS) dangers; (2) assess participants’ awareness of and specific knowledge of smoke-free (SF) policies; and (3) assess the extent to which such policies are socially enforced and gather examples of successful social enforcement.Methods Qualitative in-depth interviews and focus group discussions were conducted in Bogor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 26 publications
4
39
0
1
Order By: Relevance
“…In those venues, PM 2.5 levels were significantly greater than in non-smoking venues. As has been observed in Indonesia [20,21] and internationally [22,23,24], we found that non-enforcement of smoke-free laws fails to provide needed protection from SHS exposure for nonsmokers, including children. The PM 2.5 levels observed in this study were lower than those found in a 2009 convenience sample of 17 restaurants in Jakarta (~110 µg/m 3 ) [21] and in many similar venues sampled globally [16,25,26].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In those venues, PM 2.5 levels were significantly greater than in non-smoking venues. As has been observed in Indonesia [20,21] and internationally [22,23,24], we found that non-enforcement of smoke-free laws fails to provide needed protection from SHS exposure for nonsmokers, including children. The PM 2.5 levels observed in this study were lower than those found in a 2009 convenience sample of 17 restaurants in Jakarta (~110 µg/m 3 ) [21] and in many similar venues sampled globally [16,25,26].…”
Section: Discussionsupporting
confidence: 63%
“…While progress towards the objectives of the FCTC have been claimed by the Indonesian government [9], failure to ratify the FCTC has slowed progress toward those goals [35]. Ratification and full implementation of the FCTC by the government of Indonesia will provide a mechanism (under Article 20.4) for monitoring and responding to tobacco industry activities that undermine the implementation and enforcement of the legislation [20,37]. Evidence has shown that implementation of comprehensive bans is associated with adjustment and acceptance of bans by smokers [38], social denormalization of smoking [2], increases in voluntary home smoking bans [39,40,41], and decreased SHS exposure among children [42].…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that a major roadblock to effective social norms enforcement is the fact that individuals may feel uncomfortable with the often used model of community enforcement in which it is up to community members to inform people about the policy. A study conducted in Indonesia 35 similarly demonstrated that although individuals may report support for smoke-free policies and a willingness to ask individuals to refrain from smoking in areas where it is restricted, they continue to be reluctant to approach community leaders. The study’s authors suggest that support from government officials and increased policy enforcement might also empower community members to approach individuals smoking in restricted areas.…”
Section: Commentmentioning
confidence: 99%
“…Nonetheless, while active kretek smoking tends to be limited to men, children and women are likely to be exposed to secondhand smoke and may affect their health including the health of the unborn fetuses for pregnant women (WHO South East Asia Regional Office, 2009;WHO, 2010a). Although Kaufman et al (2014) and Nichter et al (2010) found a shift towards disapproval of smoking in public places in their study in Bogor and Palembang cities, Indonesia, they also found that people were hesitant to enforce the smoke-free policies when it came to asking men of status and/or community leaders to stop smoking.…”
Section: 6883 a Cross Sectional Study Of Kretek Smoking In Indonesiamentioning
confidence: 84%
“…In addition, the country is a party to the 2008 Resolution of the WHO South-East Asia Regional Committee that emphasized the need to strengthen national tobacco control programs and urged countries to adopt the MPOWER policy package to effectively implement the WHO Framework Convention on Tobacco Control (WHO, Regional Office for South East Asia 2008). In addition, as observed by Kaufman, Merritt, Rimbatmaja and Cohen (2014), there is already an increasing willingness among Indonesians in cities such as Bogor and Palembang cities to ask people not to smoke in public places.…”
Section: 6883 a Cross Sectional Study Of Kretek Smoking In Indonesiamentioning
confidence: 99%